URGENSI PERLINDUNGAN HUKUM TERHADAP KONSUMEN MOTOCYCLE TAXI PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN DAN TEORI MASHLAHAH - Taklima, Musa (Fakultas Syariah, 2019)
The research aims to find out Maslahah's review of people's transport activities by using a motorcycle (Ojek) and the urgency of legal protection for consumers of transportation by using a motorcycle (ojek). The research method used is normative juridical with a doctrinal approach that relies on secondary data sources consisting of primary, secondary and tertiary legal materials obtained through literature study, and analyzed using descriptive analysis method. The results of the study, first, Mashlahah's review of the Transportation of People by Motorcycle (Ojek) is a